Performance of limestone‐based sorbent for sorption‐enhanced gasification in dual interconnected fluidized bed reactors. Issue 1 (27th January 2022) - Coppola, Antonio; Sattari, Aida; Montagnaro, Fabio; Scala, Fabrizio; Salatino, Piero
Abstract: A possibility to carry out sorption‐enhanced gasification (SEG) is represented by its integration with the calcium looping concept in dual interconnected fluidized beds (DIFB). This article is focused on the sorbent CO2 uptake performance and attrition/fragmentation tendency when operating conditions simulating those of a DIFB‐SEG process are adopted. Experiments were carried out on a commercial Italian limestone in a laboratory‐scale DIFB reactor. Carbonation was carried out in a range of test conditions, including variable temperature (600–700°C) and absence/presence of steam (10% by volume); CO2 concentration was set at 10% by volume. The characterization is extended by investigating the behavior of preprocessed DIFB‐SEG samples on impact fragmentation tests, conducted in an ex situ apparatus. Tests were carried out for impact velocities in the range 17–45 m/s. Results were discussed considering both the impact velocity value and the operating conditions under which the sample was preprocessed in the fluidized bed.